Understanding Consumer Behavior: Halal Labeling and Purchase Intentions - Sani, Ageng Asmara; Rahmayanti, Dini; Kamal, Al- Haq; Ilmiah, Dunyati; Abdullah, Norhayati Binti (Journal of Digital Marketing and Halal Industry, 2023)
The rapid growth of the Muslim community in the world certainly increases the demand for halal products. This causes halal products to become a necessity. This dynamic needs to be supported by state authorities' guarantee of halal products. This study provides an overview of the role of Halal labelling in influencing individuals to consume Halal products based on their levels of religiosity, knowledge of Halal products, and attitudes towards consuming such products. Additionally, the sampling focus of this study was on Java Island, where access to information technology is widespread, facilitating ease of access to relevant information regarding Halal products. A quantitative approach was employed in this research, utilizing primary data obtained by distributing questionnaires to the residents of Java Island. The construction of the research model is reflected in an adjusted R-squared value of 54.50%, indicating that the independent variables significantly influence the dependent variable. Based on the findings of this research, both knowledge and attitudes have a positive and significant impact on the intention to consume Halal products, whereas religiosity does not. The study recommends that the government consider streamlining and reducing the costs associated with Halal labelling to make it more accessible to micro-scale producers. These measures are expected to support the development of the Halal product market and foster sustainable economic growth.